Solitary Spinal Epidural Metastasis from Gastric Cancer. (14th September 2016) - Sako, Taisei; Iida, Yasuaki; Yokoyama, Yuichirou; Tsuge, Shintaro; Hasegawa, Keiji; Wada, Akihito; Mikami, Tetsuo; Takahashi, Hiroshi
Abstract : Solitary epidural space metastasis of a malignant tumor is rare. We encountered a 79-year-old male patient with solitary metastatic epidural tumor who developed paraplegia and dysuria. The patient had undergone total gastrectomy for gastric cancer followed by chemotherapy 8 months priorly. The whole body was examined for suspected metastatic spinal tumor, but no metastases of the spine or important organs were observed, and a solitary mass was present in the thoracic spinal epidural space. The mass was excised for diagnosis and treatment and was histopathologically diagnosed as metastasis from gastric cancer. No solitary metastatic epidural tumor from gastric cancer has been reported in English. Among the Japanese, 3 cases have been reported, in which the outcome was poor in all cases and no definite diagnosis could be made before surgery in any case. Our patient developed concomitant pneumonia after surgery and died shortly after the surgery. When a patient has a past medical history of malignant tumor, the possibility of a solitary metastatic tumor in the epidural space should be considered.